Problems of interaction between philosophy and methodology of scientific knowledge in pedagogy - Bondar Volodymyr (Borys Grinchenko Kyiv Metropolitan University, 2017)
The article presents the excursion of formation and phased development the methodology of scientific knowledge as a science, in close cooperation with the scientific philosophy: its status, functions, similarities and differences in their methodological significance. It is rivaled the influence of philosophy, logic, science and scientific knowledge on the further development of the methodology as a science. Stages and the concept of its formation and development are regarded and comparative analysis of the object, method, structure and function of philosophy and methodology of science light up their role as a factor of mutual interpenetration. Discussions on these issues are going on till nowdays for benefit of these sciences and their application in the implementation of the theoretical, empirical and applied research. The findings of the research show that any science should evolve under some general laws at the empirical and theoretical levels of research. Thus, the main task of Methodology of Scientific Knowledge, a science, is the study of general methods of cognition, ways and means of formation and development of new scientific knowledge (both empirical and theoretical), general laws of the development. Therefore, the study of general methods of cognition, ways and means of the formation and development of new scientific knowledge (both empirical and theoretical), general laws of the development of nature and society is the main task of two sciences - methodology of scientific knowledge and philosophy, while reproducing extra knowledge that is required for research in certainfields of science.